Residence Time Distribution and Hydrodynamics Studies of a Swirling Fluidized Bed - Jun Li, Khor (Universiti Teknologi Petronas, 2013)
wirling fluidized bed has a lot of applications in various industries. Its ability to improve mass and heat transfer, causing vigorous mixing of particles is the main reason why it is preferred over other types of fluidized bed most of the time. Even so, the number of researches done is still little. There are still a lot of aspects in the swirling fluidized bed which are yet to be discovered. In this project, a brand new idea is implemented on the bed. It is regarding the installation of a spiral insert in the swirling fluidized bed and has never been done before. The purpose of installing the spiral insert is to increase the time spent by the particles in the reactor by forcing the particles to travel along the spiral channel before exiting the reactor. Besides, hydrodynamics study has been carried out to investigate the effect of using different types of longer twisted blades at the distributor. It is found that after minimum fluidization, the bed pressure drop of particles is lower when twisted blades are used at the distributor. However, there are several setbacks for using twisted blades.